THE SERVITIZATION PARADOX: MARKETING'S ROLE IN THE TRANSITION FROM PRODUCT-CENTRIC TO SOLUTION-CENTRIC BUSINESS MODELS - Natasya Nurkhalita; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
The transition from product-centric to solution-centric business models has become a strategic priority for organizations seeking competitive advantage in increasingly complex markets. This shift, commonly referred to as servitization, involves integrating products and services to deliver comprehensive customer solutions. However, many firms encounter the “servitization paradox,” where increased service offerings do not necessarily result in improved financial performance. This study examines the role of marketing in addressing this paradox and facilitating successful business model transformation. Drawing on a conceptual and qualitative review of literature on servitization, marketing, and business models, the paper identifies key challenges related to cost structures, capability gaps, and organizational misalignment. It argues that marketing serves as a critical value integrator by aligning customer needs with solution offerings, enabling value co-creation, and supporting the shift from transactional to relational engagement. The findings highlight the importance of redefining value propositions, strengthening customer relationships, and managing the customer lifecycle effectively. A conceptual framework is proposed to illustrate how marketing-driven strategies can mitigate the servitization paradox and enhance firm performance. The study contributes to both marketing and servitization literature by offering an integrated perspective on value creation and delivery. It concludes that strategic marketing capabilities are essential for achieving sustainable outcomes in solution-centric business models.